Energy Consumption Comparison of Halogen and LED Runway Lighting : Case Study at West Java International Airport - Sandi; Hadikusuma, Ridwan Satrio; Santoso, Dian Budhi (Techné : Jurnal Ilmiah Elektroteknika, 2025)
The increasing inefficiency and high costs of traditional halogen runway lighting systems have prompted a need for sustainable alternatives. This study investigates the performance, energy efficiency, and economic impact of halogen versus LED runway edge lights at West Java International Airport. Utilizing the Constant Current Regulator (CCR) and Cost Benefit Analysis (CBA) methods, the research highlights the advantages of LED lighting systems, which include superior energy efficiency, longer lifespan, and faster responsiveness. The findings reveal that adopting LED lights significantly reduces operational and maintenance costs while enhancing flight safety and environmental sustainability. Furthermore, the transition to LED lighting offers long-term financial benefits for airports by minimizing energy consumption and maintenance demands. Based on the results, this study provides actionable recommendations for airport management to upgrade to energy-efficient LED systems, ensuring improved operational efficiency and sustainability in runway lighting infrastructure. The insights gained from this research can serve as a valuable reference for decision-makers in optimizing airport lighting systems effectively and responsibly.